Research progress of assessment tool and prevention of incontinence-associated dermatitis (失禁相关性皮炎评估工具和预防的研究进展) - MIAO Wenjing (苗文静); GUO Fengjuan (郭凤娟); CHEN Liuwen (陈柳文) (中西医结合护理)
Incontinence-associated dermatitis (IAD) is a common type of irritant contact dermatitis, and accurate assessment and diagnosis are important for early prevention and treatment. Based on the reviewing the relevant studies, this paper summarized the research progress of assessment tool and prevention of incontinence-associated dermatitis, in order to provide reference for clinical nurse to improve the accuracy in diagnosis and early intervention on IAD. (失禁相关性皮炎(IAD)是一种皮肤炎症, 正确的评估和诊断对早期防治非常重要。本文通过检索查阅文献, 收集、整理、分析了近年来与IAD相关的评估工具和预防措施, 以期为临床护理人员提高失禁相关性皮炎评估准确性和早期干预提供参考依据。)